2010
DOI: 10.1042/cbi20100114
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin and Rho GTPases as downstream targets of TGF-β1 during pulp repair

Abstract: TGF-β1 (transforming growth factor-β1) plays a central role in regulating proliferation, migration and differentiation of dental pulp cells during the repair process after tooth injury. Our previous study showed that p38 mitogen-activated protein kinase may act downstream of TGF-β1 signalling to effect the differentiation of dental pulp cells. However, the molecular mechanisms that trigger and regulate the process remain to be elucidated. TGF-β1 interacts with signalling pathways such as Wnt/β-catenin and Rho … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…As an example, the literature shows that Rho and ROCK participate with the β-catenin and TGF-β signaling pathways, even though the TGF-β or Wnt proteins are absent [35][36]. In other cases ROCK acts downstream when Wnt and TGF-β are present [37]. Therefore, we suggest that ROCK has the ability to serve as an intermediate between these pathways, possibly controlling this balance between active/inactive downstream states (Figure 5L).…”
Section: Discussionmentioning
confidence: 83%
“…As an example, the literature shows that Rho and ROCK participate with the β-catenin and TGF-β signaling pathways, even though the TGF-β or Wnt proteins are absent [35][36]. In other cases ROCK acts downstream when Wnt and TGF-β are present [37]. Therefore, we suggest that ROCK has the ability to serve as an intermediate between these pathways, possibly controlling this balance between active/inactive downstream states (Figure 5L).…”
Section: Discussionmentioning
confidence: 83%
“…For example, previous studies have shown that TGF-␤1 is a central factor released in high amounts during pulp repair, regulating migration of DPSCs toward the injured site [49] and subsequent differentiation into odontoblastic cells producing reparative dentin [50]. On the other hand, ␤-catenin has been found to mediate the downstream events of TGF␤1 signaling, by its translocation into the nucleus and interaction with LEF/TCF to regulate gene expression during pulp repair [18]. In another study it was also shown that pulp cavity preparation procedures directly activate ␤-catenin accumulation in pulp cells beneath the cavity [51].…”
Section: Discussionmentioning
confidence: 96%
“…During tooth initiation and morphogenesis, Wnt3, Wnt7b, Wnt10a and Wnt10b, in conjunction with sonic hedgehog (SHH), regulate cell proliferation, migration and differentiation [16,17]. Importantly, TGF-␤1 has been shown to interact with Wnt/␤-catenin signaling to induce various biological effects during pulp repair [18].…”
Section: Introductionmentioning
confidence: 99%
“…So far, only a few reports give emphasis on the area for pathways serving functions in pulp repair. [ 33 ]…”
Section: Dentine and Pulp And β Cateninmentioning
confidence: 99%